Symmetric Remote Two-Qubit Preparation via Positive Operator-Valued Measure (Journal of Atomic and Molecular Sciences, 2010)
I present a novel tripartite scheme for remotely preparing an arbitrary two-qubit state with two three-qubit entanglements. By using a proper positive operator-valued measure (POVM), it is shown the remote two-qubit preparation can be realized in either distant ministrant's place in a probabilistic manner via their collaboration. I also explore its applications to six special ensembles of state in detail. The extensive investigations shows that the remote preparation can be achieved with higher probability provided that the prepared state belongs to the six special ensembles.
Keywords: remote state preparation; three-qubit entanglement; positive operator-valued measure; unitary operationd.